Where to draw the line? Using movement data to inform protected area design and conserve mobile species. (June 2019) - Choi, Chi-Yeung; Peng, He-Bo; He, Peng; Ren, Xiao-Tong; Zhang, Shen; Jackson, Micha V.; Gan, Xiaojing; Chen, Ying; Jia, Yifei; Christie, Maureen; Flaherty, Tony; Leung, Kar-Sin Katherine; et al.
Abstract: Protected areas (PAs) are a cornerstone of modern conservation. For PAs that are established to conserve mobile species, it is important to cover all the key areas regularly used by these species. However, zonation and boundaries of PAs have often been established with limited knowledge of animal movements, leaving the effectiveness of some PAs doubtful. We used radio tracking data to evaluate the extent to which two coastal PAs in mainland China encompassed the full range of habitats used by migratory shorebirds during non-breeding seasons. The core zone (highest restriction on human activities) of the Yalu Jiang Estuary National Nature Reserve (Liaoning) incorporated only 22 ± 6% (n = 34) of the diurnal home range (95% kernel density) of the endangered great knots Calidris tenuirostris . In contrast, the core zone of Chongming Dongtan (Shanghai) incorporated 73 ± 24% (n = 25) of the home range of dunlins Calidris alpina . During high tide, great knots in Yalu Jiang mostly occurred in the experimental zone (least restriction on human activities) or sometimes outside the PA boundary altogether, where the birds could face substantial threats. By investigating satellite tracking records, consulting published literature, interviewing local experts and mapping habitat composition in different coastal PAs in China, we found that wet artificial supratidal habitats were frequently used by migratory shorebirds but the coverage of these habitats in coastal PAs was low. These PA boundaries and/or zonations should be revised to conserve mobile species more effectively. With the increasing number of tracking studies, analysing the spatial relationships between PAs and the movement ranges of mobile species can increasingly inform the development of a representative, comprehensive PA network.